IL-1β-converting enzyme (caspase-1) in intestinal inflammation - Siegmund, Britta (The National Academy of Sciences, 2001)
IL-1β-converting enzyme (ICE; caspase-1) is the intracellular protease that cleaves the precursors of IL-1β and IL-18 into active cytokines. In the present study, the effect of ICE deficiency was evaluated during experimental colitis in mice. In acute dextran sulfate sodium-induced colitis, ICE-deficient (ICE KO) mice exhibited a greater than 50% decrease of the clinical scores weight loss, diarrhea, rectal bleeding, and colon length, whereas daily treatment with IL-1 receptor antagonist revealed a modest reduction in colitis severity. To further characterize the function of ICE and its role in intestinal inflammation, chronic colitis was induced over a 30-day time period. During this chronic time course, ICE KO mice exhibited a near complete protection, as reflected by significantly reduced clinical scores and almost absent histological signs of colitis. Consistently, colon shortening occurred only in dextran sulfate sodium-exposed wild-type mice but not in ICE KO mice. Protection was accompanied by reduced spontaneous release of the proinflammatory cytokines IL-18, IL-1β, and IFN-γ from total colon cultures. In addition, flow cytometric analysis of isolated mesenteric lymph node cells revealed evidence of reduced cell activation in ICE KO mice as evaluated by surface expression of CD3 CD69 and CD4 CD25. We conclude that inhibition of ICE represents a novel anti-inflammatory strategy for intestinal inflammation.